Mechanisms Underlying the Pathogenic and Endophytic Lifestyles in Diaporthe: An Omics-Based Approach - Sandra Hilário; Micael F. M. Gonçalves (Horticulturae, 2023)
The genus Diaporthe encompasses important plant pathogens, endophytes, and saprobes that are widely distributed in tropical and temperate regions. An accurate detection and identification of plant pathogens not only allows correct disease diagnosis but also increases the accuracy of taxonomic ambiguities for fungal-plant interactions purposes. Multi-omics approaches applied to this genus may represent valuable tools to unravel molecular mechanisms involved in the infection processes. Additionally, omics can provide adaptation patterns that make pathogens thrive under changing environmental conditions, and insights into the dual pathogen-endophyte lifestyle. Therefore, all published data covered in this literature review represents an important contribution to deepen the knowledge on the importance of omics in fungal-plant interactions. This accumulating evidence will speed up the research on formulating new strategies to control plant pathologies, to assist in the exploitation of endophytes for their function in plant hosts, and to underline molecular factors of fungal pathogenicity and endophytism in the genus Diaporthe.